Cellulose polymer, preparation method and application thereof, and water-based drilling fluid
By introducing specific anionic and cationic substitution groups into cellulose polymers, the degree of substitution is optimized, and the problem of reacting cellulose polymers with metal ions in water-based drilling fluids to generate gels is solved, and metal salts are achieved at high concentrations High-efficiency filter loss reduction effect in the environment.
Patent Information
- Application Number
- CN202310959352.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
The existing polyanionic cellulose filtration loss agents are prone to react with metal ions in water-based drilling fluid to produce gels, resulting in a serious reduction in the use effect.
Design a cellulose-based polymer, by introducing anionic substituent group - CH2COONa and specific cationic substituent groups into the a-cellulose body, the degree of substitution is optimized to improve the resistance to metal ion and reduce gel action.
The cellulose-based polymer significantly reduces the gel reaction with metal ions in a water-based environment, maintains good performance, and can effectively reduce the API filtration loss in water-based drilling fluid containing high concentrations of polyvalent metal salts.
Smart Images

Figure CN119431611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical additives for oilfield drilling, and in particular to a cellulose polymer and a preparation method and application thereof, and a water-based drilling fluid. Background Art
[0002] Cellulose, as a natural polymer material, is a linear polymer composed of many D-pyranose glucosides connected by β-(1,4) glycosidic bonds. It is widely used in the field of chemical production due to its advantages of being green, environmentally friendly, low-priced and easy to process. Polyanionic cellulose, as a water-soluble anionic cellulose ether, is prepared from natural fibers such as cotton through refining, alkalization and etherification processes. Polyanionic cellulose is often used as a fluid loss reducer in the field of oil drilling, which plays a role in improving mud cake quality, controlling fluid loss and adjusting the rheological properties of drilling fluids.
[0003] The chemical composition of polyanionic cellulose is mainly sodium carboxymethyl cellulose, which can dissociate into long-chain molecules containing carboxyl groups after being dissolved in water, so it is called anionic cellulose ether. At present, in the field of water-based drilling, when drilling to high-mineralization formations, sodium carboxymethyl cellulose, which originally plays the role of increasing cutting, viscosity and reducing filtration, will react with metal ions (iron ions, copper ions, aluminum ions, lanthanum ions, cerium ions, nickel ions, zinc ions, etc.) in the formation to form a complex after dissociation in the water phase, forming a three-dimensional network structure of the gel, which seriously reduces the effect of sodium carboxymethyl cellulose in water-based drilling fluids.
[0004] Therefore, the development of anti-gel cellulose-based fluid loss reducers is of great significance for expanding the application effect and scope of this type of environmentally friendly drilling additives. Summary of the invention
[0005] The purpose of the present invention is to provide a cellulose polymer, a preparation method and application thereof, and a water-based drilling fluid in order to solve the problem that the existing polyanionic cellulose fluid loss reducer has insufficient resistance to metal ions and is easy to react with metal ions to produce gel, thereby seriously affecting the use effect in water-based drilling fluid.
[0006] In order to achieve the above object, the present invention provides a cellulose polymer in the first aspect, which comprises: an a-cellulose main body and a plurality of substituent groups -R and -CH 2 COONa, the substituent group is connected to some of the hydroxyl oxygens contained in the a-cellulose body;
[0007] Wherein, the -R is selected from -C 6 H 15 ClNO, -C 5 H 13 ClN and -C 6 H15 At least one of ClN;
[0008] In the polymer, -R and -CH 2 The degree of substitution of COONa satisfies the following relationship:
[0009] 0.8≤(DS-CH 2 COONa+DS -R )≤1.6, DS-CH 2 COONa / DS -R =1:(0.05-0.15).
[0010] A second aspect of the present invention provides a method for preparing a cellulose polymer, comprising:
[0011] (1) in the presence of an organic solvent and an alkali solution, subjecting the cellulose raw material to an alkalization treatment to obtain alkalized cellulose;
[0012] (2) subjecting the alkalized cellulose to a first etherification treatment in the presence of a first etherifying agent to obtain a first product;
[0013] (3) activating the first etherification product in the presence of an activating agent to obtain a second product;
[0014] (4) subjecting the second product to a second etherification treatment in the presence of a second etherifying agent to obtain a cellulose polyether polymer.
[0015] The third aspect of the present invention provides a cellulose polymer obtained by the method described in the second aspect.
[0016] The fourth aspect of the present invention provides a water-based drilling fluid comprising the cellulose polymer described in the first aspect or the third aspect.
[0017] The fifth aspect of the present invention provides use of the cellulose polymer described in the first aspect or the third aspect as a fluid loss reducer in drilling fluid.
[0018] Through the above technical scheme, the present invention adopts a specific molecular structure design to simultaneously introduce anionic substituent groups -CH 2COONa and specific cationic substituent groups are used to replace the hydrogen atoms in some hydroxyl groups contained in the main body of a-cellulose, and the substitution degree of the anionic substituent groups and the cationic substituent groups is optimized and adjusted to obtain a modified cellulose polymer. The cellulose polymer provided by the present invention utilizes the electrical repulsion between the specific cationic groups contained in it and metal ions (iron ions, copper ions, aluminum ions, lanthanum ions, cerium ions, nickel ions, zinc ions, etc.), so that the gelation between the cellulose polymer and the above-mentioned metal ions is greatly reduced, and it has the ability to resist metal ions (anti-gel), and can thus maintain its own performance well in a water-based environment containing metal ions. The cellulose polymer provided by the present invention is used as a fluid loss reducer in a water-based drilling fluid containing 1% high-concentration multivalent metal salts, which can achieve an API fluid loss of less than 16mL in the drilling fluid, effectively solving the problem of performance failure of ordinary polyanionic cellulose fluid loss reducers in the process of drilling in formations containing high-concentration metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0020] Figure 1 This is the infrared spectrum of the cellulose polymer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0023] In a first aspect, the present invention provides a cellulose polymer, which comprises: an a-cellulose main body and a plurality of substituent groups -R and -CH 2 COONa, the substituent group is connected to some of the hydroxyl oxygens contained in the a-cellulose body;
[0024] Wherein, the -R is selected from -C 6 H 15 ClNO, -C 5 H 13 ClN and -C6 H 15 At least one of ClN;
[0025] In the polymer, -R and -CH 2 The degree of substitution of COONa satisfies the following relationship:
[0026] 0.8≤(DS-CH 2 COONa+DS -R )≤1.6, DS-CH 2 COONa / DS -R =1:(0.05-0.15).
[0027] According to the present invention, the a-cellulose main body is a cyclic repeating segment main structure composed of C and O possessed by the well-known a-cellulose, as shown in formula (1),
[0028]
[0029] In formula (1), a secondary hydroxyl group is connected to the 2nd carbon atom and the 3rd carbon atom of the six-membered heterocyclic ring composed of C and O, and a primary hydroxyl group is connected to the 6th carbon atom. The cellulose polymer provided by the present invention is a cellulose polymer in which the hydroxyl hydrogen of some hydroxyl groups connected to the a-cellulose body is replaced by -R and -CH 2 COONa (i.e., after substitution, -R and -CH 2 COONa is connected to the hydroxyl oxygen respectively). In the present invention, the -R and -CH 2 The position of the hydroxyl hydrogen substituted by COONa is not particularly limited and can be any hydroxyl hydrogen on any hydroxyl group in the above formula (1), as long as the -R and -CH in the cellulose polymer can be replaced. 2 The degree of substitution of COONa can satisfy the following relationship: 0.8≤(DS-CH 2 COONa+DS -R )≤1.6, DS-CH 2 COONa / DS -R =1:(0.05-0.15).
[0030] In the present invention, the hydroxyl oxygen refers to an oxygen atom contained in a hydroxyl group (ie, "-OH"), and the hydroxyl hydrogen refers to a hydrogen atom contained in a hydroxyl group.
[0031] In the present invention, the degree of substitution (DS) refers to the average number of hydroxyl hydrogens substituted by substituted groups in each carbon-oxygen six-membered heterocyclic structural unit in the cellulose polymer, which can be measured by the ash method specified in GB / T5005-2010 (Drilling Fluid Material Specification).
[0032] According to the present invention, for the -R, wherein -C 6 H 15 The structural formula of ClNO is shown in formula (2), -C 5 H 13 The structural formula of ClN is shown in formula (3), -C 6 H 15 The structural formula of ClN is shown in formula (4);
[0033]
[0034] In formula (2), formula (3) and formula (4), * represents the bonding position of the substituent group to the hydroxyl oxygen.
[0035] In the cellulose polymer provided by the present invention, the -R is a cationic substituent group. The inventors of the present invention have found that by replacing the hydroxyl hydrogen, an anionic substituent group -CH 2 COONa and specific cationic substituent groups can greatly inhibit the complexation reaction between the polymer and the above metal ions in water by utilizing the electrical repulsion between the cationic groups and multivalent metal ions (iron ions, copper ions, aluminum ions, lanthanum ions, cerium ions, nickel ions, zinc ions, etc.), thereby preventing the formation of gel, and making the polymer less affected by high concentrations of metal ions in a water-based environment, that is, having excellent metal ion resistance. According to a preferred embodiment of the present invention, the -R is selected from -C 6 H 15 ClNO and / or -C 6 H 15 ClN can make the cellulose polymer have better resistance to metal ions.
[0036] According to the present invention, in the cellulose polymer, the -R and -CH 2 The substitution degree of COONa satisfies the above-defined relationship. Further, DS-CH 2 COONa / DS -R =1: (0.1-0.15), which can make the cellulose polymer have a further improved ability to resist metal ions.
[0037] According to the present invention, the degree of polymerization of the cellulose polymer is 70-2600. Too high a degree of polymerization will result in too high an apparent viscosity of the cellulose polymer, and too low a degree of polymerization will result in too low an apparent viscosity of the cellulose polymer, affecting its viscosity-increasing and shear-enhancing effects. In the present invention, the degree of polymerization can be determined by the method specified in GB / T 9107-1999 (refined cotton).
[0038] According to the present invention, the apparent viscosity of the cellulose polymer is 10-2000 mPa·s. In the present invention, the apparent viscosity can be measured by the method specified in GB / T 5005-2010 (Specification for Drilling Fluid Materials).
[0039] The cellulose polymer provided by the present invention has good viscosity increasing and water retention effects when dissolved in water, and has excellent resistance to metal ions, and rarely undergoes complexation reaction with metal ions. It is used as a fluid loss reducer in water-based drilling fluid, and can well solve the problem of performance failure of ordinary polyanionic cellulose fluid loss reducers during drilling in formations containing high concentrations of metal ions. Specifically, the cellulose polymer provided by the present invention is applied to a water-based drilling fluid containing 1% high-concentration multivalent metal salt (the metal ions in the multivalent metal salt can be iron ions, copper ions, aluminum ions, lanthanum ions, cerium ions, nickel ions or zinc ions) (that is, the content of the multivalent metal salt in the water-based drilling fluid reaches 1% by weight), and the API fluid loss of the drilling fluid can be achieved to be less than 16mL.
[0040] According to a most preferred embodiment of the present invention, the polymer comprises: an a-cellulose main body and a plurality of substituent groups -C 6 H 15 ClNO and -CH 2 COONa, and -C 6 H 15 ClNO and -CH 2 COONa connects some of the hydroxyl oxygens contained in the a-cellulose body; wherein -C 6 H 15 ClNO and -CH 2 The substitution degree of COONa satisfies: 1.3≤(DS-CH 2 COONa+DS-C 6 H 15 ClNO)≤1.6, DS-CH 2 COONa / DS-C 6 H 15 ClNO=1: (0.1-0.12) The cellulose polymer of the best embodiment is used as a fluid loss reducer in a water-based drilling fluid containing 1% high-concentration multivalent metal salt, and the API fluid loss of the drilling fluid can be less than 10 mL.
[0041] A second aspect of the present invention provides a method for preparing a cellulose polymer, comprising:
[0042] (1) in the presence of an organic solvent and an alkali solution, subjecting the cellulose raw material to an alkalization treatment to obtain alkalized cellulose;
[0043] (2) subjecting the alkalized cellulose to a first etherification treatment in the presence of a first etherifying agent to obtain a first product;
[0044] (3) activating the first etherification product in the presence of an activating agent to obtain a second product;
[0045] (4) subjecting the second product to a second etherification treatment in the presence of a second etherifying agent to obtain a cellulose polyether polymer.
[0046] According to the present invention, in step (1), the cellulose raw material is selected from refined cotton (the main component of which is α-cellulose) or a cellulose extract containing α-cellulose other than refined cotton.
[0047] According to the present invention, when the cellulose raw material is a cellulose extract containing a-cellulose other than refined cotton, the cellulose raw material is preferably purified before the alkalization treatment so that the content of a-cellulose in the purified raw material reaches 90-99% by weight.
[0048] According to the present invention, preferably, the polymer of α-cellulose in the cellulose raw material is 300-2600.
[0049] According to the present invention, in step (1), the organic solvent is preferably an alcohol solvent, and more preferably ethanol and / or isopropanol.
[0050] According to the present invention, in step (1), the alkali solution may be a conventional alkaline aqueous solution for alkalizing cellulose, such as an aqueous solution of sodium hydroxide. Preferably, the concentration of the aqueous solution of sodium hydroxide is 30-45% by weight.
[0051] According to the present invention, in step (1), in order to obtain a better alkalization treatment effect, preferably, the weight ratio of the organic solvent: the solute alkali in the alkali solution (such as NaOH): the cellulose raw material is (8-30): (0.6-1.6):1.
[0052] According to the present invention, in step (1), in order to better control the alkalization treatment process and obtain a better treatment effect, water can be added to the reaction system according to the progress of the alkalization reaction. The operation and the amount of added water can adopt methods and parameters known in the art, and the present invention has no particular limitation on this.
[0053] According to the present invention, in step (1), the alkalization treatment can be carried out by conventional operation methods, and the present invention has no particular limitation on this. Preferably, the conditions of the alkalization treatment include: a temperature of 10-30°C and a time of 1-2h.
[0054] According to the present invention, in step (2), the first etherifying agent is selected from at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride (CAS No.: 3327-22-8), 3-chloropropyltrimethylammonium chloride (CAS No.: 1936-95-4) and 2-chloroethyltrimethylammonium chloride (CAS No.: 999-81-5), more preferably 3-chloro-2-hydroxypropyltrimethylammonium chloride and / or 3-chloropropyltrimethylammonium chloride, most preferably 3-chloro-2-hydroxypropyltrimethylammonium chloride.
[0055] According to the present invention, in step (2), preferably, the weight ratio of the first etherifying agent to the cellulose raw material in step (1) is (0.1-0.25):1.
[0056] According to the present invention, in step (2), for the first etherification treatment, the alkalized cellulose can be mixed with a first etherifying agent, and an etherification reaction can be carried out at a certain temperature to introduce a specific cationic substituent group into the a-cellulose body by replacing hydroxyl hydrogen to obtain a first product. Preferably, the conditions of the first etherification treatment include: a temperature of 40-80°C and a time of 0.5-3h. Further preferably, the conditions of the first etherification treatment include: a temperature of 50-75°C and a time of 1-2h.
[0057] According to the present invention, in step (3), preferably, the activator is selected from at least one of triethylammonium chloride, tetraethylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium bromide, benzyltrimethylammonium chloride and benzyltriethylammonium chloride.
[0058] According to the present invention, in step (3), preferably, the weight ratio of the activating agent to the cellulose raw material in step (1) is (0.02-0.1):1.
[0059] According to the present invention, in step (3), for the activation treatment, the first product can be mixed with an activator and an activation reaction can be carried out at a certain temperature, so that the hydroxyl groups on the cellulose molecular ring that are not involved in the etherification during the first etherification treatment process maintain a high reaction activity to obtain a second product. Preferably, the conditions of the activation treatment include: a temperature of 30-50°C and a time of 0.5-1h.
[0060] According to the present invention, in step (4), the second etherifying agent is selected from chloroacetic acid and / or sodium chloroacetate.
[0061] According to the present invention, in step (4), preferably, the weight ratio of the second etherifying agent to the cellulose raw material in step (1) is (0.5-1.8):1.
[0062] According to the present invention, in step (4), for the second etherification treatment, the second product can be mixed with a second etherifying agent, and an etherification reaction can be carried out at a certain temperature to continue to introduce -CH in the a-cellulose body by replacing the hydroxyl hydrogen. 2 Preferably, the conditions of the second etherification treatment include: a temperature of 50-80°C and a time of 1-3 hours.
[0063] According to a preferred embodiment of the present invention, the conditions of the second etherification treatment include: reacting at a temperature of 50-55°C for 1-1.5 hours, then heating up and reacting at 75-80°C for 1-1.5 hours.
[0064] According to the present invention, the method for preparing the cellulose polymer further comprises neutralizing, filtering, washing and drying the product system obtained after the second etherification treatment to obtain the cellulose polyether polymer.
[0065] The third aspect of the present invention provides a cellulose polymer obtained by the method described in the second aspect.
[0066] According to the present invention, the structure, composition and properties of the cellulose polymer prepared by the method described in the second aspect are the same as the cellulose polymer described in the first aspect of the present invention, and will not be described in detail here.
[0067] The fourth aspect of the present invention provides a water-based drilling fluid comprising the cellulose polymer described in the first aspect or the third aspect.
[0068] The water-based drilling fluid provided by the present invention contains the cellulose polymer provided by the present invention, so that the water-based drilling fluid has excellent metal ion resistance and can maintain a low filtration loss during drilling in a formation containing high concentrations of metal ions. According to the present invention, preferably, based on the total weight of the water-based drilling fluid, the content of the cellulose polymer in the water-based drilling fluid is 0.2-3% by weight.
[0069] The fifth aspect of the present invention provides use of the cellulose polymer described in the first aspect or the third aspect as a fluid loss reducer in drilling fluid.
[0070] The present invention will be described in detail below through preparation examples and examples. In the following preparation examples and examples, unless otherwise specified, all are conventional methods; the reagents and materials described, unless otherwise specified, can be obtained from commercial sources.
[0071] Example 1
[0072] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 300-500), isopropanol, and a NaOH aqueous solution (concentration of 45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 10° C. for 2 h to obtain alkalized cellulose;
[0073] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0074] (2) adding an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 1.5 hours to obtain a first product;
[0075] Wherein, the weight ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the refined cotton in step (1) is 0.15:1;
[0076] (3) adding tetraethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0077] Wherein, the weight ratio of tetraethylammonium chloride to the refined cotton in step (1) is 0.05:1;
[0078] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and continuing the etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it by suction, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again by suction, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P1);
[0079] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.9:1.
[0080] The test showed that the apparent viscosity of P1 was 140 mPa·s and the degree of polymerization was 370;
[0081] The infrared spectrum test of P1 shows the following results: Figure 1 As shown, Figure 1 Visible in the middle, 1636cm -1 、1322cm -1 There is a characteristic absorption peak near 6 H 15 ClNO, -CH 2 COONa achieves linkage with hydroxyl oxygen;
[0082] In P1, (DS-CH 2 COONa+DS-C 6 H 15 ClNO)=1.60,DS-CH2 COONa / DS-C 6 H 15 ClNO=1:0.12.
[0083] Example 2
[0084] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 300-500), isopropanol, and a NaOH aqueous solution (45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0085] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0086] (2) adding an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 1 h to obtain a first product;
[0087] Wherein, the weight ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the refined cotton in step (1) is 0.1:1;
[0088] (3) adding tetraethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0089] Wherein, the weight ratio of tetraethylammonium chloride to the refined cotton in step (1) is 0.05:1;
[0090] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P2);
[0091] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.9:1.
[0092] The test showed that the apparent viscosity of P2 was 110 mPa·s and the degree of polymerization was 350;
[0093] In P2, (DS-CH 2 COONa+DS-C 6 H 15 ClNO)=1.36,DS-CH 2 COONa / DS-C 6 H 15 ClNO=1:0.10.
[0094] Example 3
[0095] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 500-800), isopropanol, and a NaOH aqueous solution (concentration of 45 weight %) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0096] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0097] (2) adding an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 3 hours to obtain a first product;
[0098] Wherein, the weight ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the refined cotton in step (1) is 0.2:1;
[0099] (3) adding tetraethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0100] Wherein, the weight ratio of tetraethylammonium chloride to the refined cotton in step (1) is 0.05:1;
[0101] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P3);
[0102] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.9:1.
[0103] The test showed that the apparent viscosity of P3 was 230 mPa·s and the degree of polymerization was 620;
[0104] In P3, (DS-CH 2 COONa+DS-C 6 H 15 ClNO)=1.28,DS-CH 2 COONa / DS-C 6 H 15 ClNO=1:0.15.
[0105] Example 4
[0106] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 500-800), isopropanol, and a NaOH aqueous solution (concentration of 45 weight %) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0107] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0108] (2) adding an aqueous solution of 3-chloropropyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 40° C. for 3 h to obtain a first product;
[0109] Wherein, the weight ratio of 3-chloropropyltrimethylammonium chloride aqueous solution to the refined cotton in step (1) is 0.2:1;
[0110] (3) adding tetrabutylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 0.5 h to obtain a second product;
[0111] Wherein, the weight ratio of tetramethylammonium chloride to the refined cotton in step (1) is 0.08:1;
[0112] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P4);
[0113] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.9:1.
[0114] The test showed that the apparent viscosity of P4 was 260 mPa·s and the degree of polymerization was 590;
[0115] In P4, (DS-CH 2 COONa+DS-C 6 H 15 ClN)=1.23,DS-CH 2 COONa / DS-C 6 H 15 ClN=1:0.14.
[0116] Example 5
[0117] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 500-800), isopropanol, and a NaOH aqueous solution (concentration of 45 weight %) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0118] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0119] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 2 h to obtain a first product;
[0120] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the refined cotton in step (1) is 0.25:1;
[0121] (3) adding benzyltrimethylammonium chloride to the product obtained in step (2), and performing activation treatment at 30° C. for 0.5 h to obtain a second product;
[0122] Wherein, the weight ratio of benzyltrimethylammonium chloride to the refined cotton in step (1) is 0.09:1;
[0123] (4) adding an isopropanol solution of sodium chloroacetate to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P5);
[0124] The weight ratio of sodium chloroacetate to the refined cotton in step (1) is 1.12:1.
[0125] The test showed that the apparent viscosity of P5 was 350 mPa·s and the degree of polymerization was 580;
[0126] In P5, (DS-CH 2 COONa+DS-C 5 H 13 ClN)=1.20,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.15.
[0127] Example 6
[0128] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 1000-1400), ethanol, and a NaOH aqueous solution (with a concentration of 45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 30° C. for 1 h to obtain alkalized cellulose;
[0129] Among them, the weight ratio of ethanol: solute NaOH: refined cotton is 24:1.6:1;
[0130] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 80° C. for 0.5 h to obtain a first product;
[0131] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the refined cotton in step (1) is 0.15:1;
[0132] (3) adding triethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0133] Wherein, the weight ratio of triethylammonium chloride to the refined cotton in step (1) is 0.02:1;
[0134] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 0.5 h, then raising the temperature to 75° C. and performing an etherification treatment for 0.5 h to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 h to obtain a cellulose polymer (denoted as P6);
[0135] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 1.8:1.
[0136] The test showed that the apparent viscosity of P6 was 620 mPa·s and the degree of polymerization was 1100;
[0137] In P6, (DS-CH 2 COONa+DS-C 5 H 13 ClN)=0.95,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.05.
[0138] Example 7
[0139] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 2000-2600), isopropanol, and a NaOH aqueous solution (concentration of 30 weight %) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0140] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 8:0.6:1;
[0141] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 1 h to obtain a first product;
[0142] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the refined cotton in step (1) is 0.15:1;
[0143] (3) adding benzyltriethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0144] Wherein, the weight ratio of benzyltriethylammonium chloride to the refined cotton in step (1) is 0.1:1;
[0145] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 2 h, then raising the temperature to 80° C. and performing an etherification treatment for 1 h to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90 wt %, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 h to obtain a cellulose polymer (denoted as P7);
[0146] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.5:1.
[0147] After testing, the apparent viscosity of P7 is 2000mPa·s and the degree of polymerization is 2320;
[0148] In P7, (DS-CH 2 COONa+DS-C 5 H 13 ClN)=0.92,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.06.
[0149] Example 8
[0150] (1) Purifying rice straw to obtain a purified material (the content of a-cellulose in the purified material is 92% by weight, wherein the degree of polymerization of a-cellulose contained is 300-500), adding the purified material, isopropanol, and an aqueous solution of NaOH (with a concentration of 45% by weight) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0151] Among them, the weight ratio of isopropanol: solute NaOH: purified material is 30:0.81:1;
[0152] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 1 h to obtain a first product;
[0153] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the purified material in step (1) is 0.12:1;
[0154] (3) adding tetrabutylammonium bromide to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0155] Wherein, the weight ratio of tetraethylammonium chloride to the purified material in step (1) is 0.05:1;
[0156] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as P8);
[0157] Wherein, the weight ratio of chloroacetic acid to the purified material in step (1) is 0.9:1.
[0158] The test showed that the apparent viscosity of P8 was 10 mPa·s and the degree of polymerization was 70;
[0159] In P8, (DS-CH 2 COONa+DS-C 5 H 13 ClN)=1.52,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.09.
[0160] Comparative Example 1
[0161] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 500-800), ethanol, and a NaOH aqueous solution (with a concentration of 45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0162] Among them, the weight ratio of ethanol: solute NaOH: refined cotton is 24:0.81:1;
[0163] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 0.5 h to obtain a first product;
[0164] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the refined cotton in step (1) is 0.15:1;
[0165] (3) adding triethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0166] Wherein, the weight ratio of triethylammonium chloride to the refined cotton in step (1) is 0.02:1;
[0167] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 h, then raising the temperature to 70° C. and performing an etherification treatment for 0.5 h to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 h to obtain a cellulose polymer (denoted as D1);
[0168] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 1.8:1.
[0169] The test showed that the apparent viscosity of D1 was 72 mPa·s and the degree of polymerization was 590;
[0170] In D1, (DS-CH 2 COONa+DS-C 5 H 13 ClN)=0.78,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.05.
[0171] Comparative Example 2
[0172] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 300-500), isopropanol, and a NaOH aqueous solution (concentration of 45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0173] Among them, the weight ratio of isopropyl alcohol: solute NaOH: refined cotton is 24:0.81:1;
[0174] (2) adding tetraethylammonium chloride activator to the product obtained in step (1), and performing activation treatment at 50° C. for 1 h to obtain an activated product;
[0175] Wherein, the weight ratio of tetraethylammonium chloride activator to the refined cotton in step (1) is 0.05:1;
[0176] (3) adding an isopropanol solution of chloroacetic acid to the activated product obtained in step (2), performing an etherification treatment at 50° C. for 1 h, then raising the temperature to 75° C. and performing an etherification treatment for 1 h to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 h to obtain a cellulose polymer (denoted as D2);
[0177] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.9:1.
[0178] The apparent viscosity of D2 was tested to be 10 mPa·s and the degree of polymerization was 330;
[0179] In D2, DS-C 6 H 15 ClNO=0,DS-CH 2 COONa=1.2.
[0180] Comparative Example 3
[0181] (1) adding purified cotton (containing a-cellulose with a polymerization degree of 500-800), ethanol, and a NaOH aqueous solution (with a concentration of 45 wt%) into a four-necked flask, stirring and mixing, and alkalizing at 20° C. for 1 h to obtain alkalized cellulose;
[0182] Among them, the weight ratio of ethanol: solute NaOH: refined cotton is 24:0.81:1;
[0183] (2) adding an aqueous solution of 2-chloroethyltrimethylammonium chloride to the product obtained in step (1), and performing an etherification treatment at 50° C. for 0.5 h to obtain a first product;
[0184] Wherein, the weight ratio of 2-chloroethyltrimethylammonium chloride to the refined cotton in step (1) is 0.08:1;
[0185] (3) adding triethylammonium chloride to the product obtained in step (2), and performing activation treatment at 50° C. for 1 h to obtain a second product;
[0186] Wherein, the weight ratio of triethylammonium chloride to the refined cotton in step (1) is 0.02:1;
[0187] (4) adding an isopropanol solution of chloroacetic acid to the product obtained in step (3), performing an etherification treatment at 50° C. for 1 hour, then raising the temperature to 75° C. and performing an etherification treatment for 1 hour to obtain a product system; then cooling the product system, neutralizing it with acetic acid, filtering it, washing it with an ethanol aqueous solution with a concentration of 90% by weight, and filtering it again, and vacuum drying the obtained product at 80° C. for 24 hours to obtain a cellulose polymer (denoted as D3);
[0188] The weight ratio of chloroacetic acid to the refined cotton in step (1) is 0.6:1.
[0189] The test showed that the apparent viscosity of D3 was 102 mPa·s and the degree of polymerization was 570;
[0190] In D3, (DS-CH 2 COONa+DS-C 5 H13 ClN)=0.95,DS-CH 2 COONa / DS-C 5 H 13 ClN=1:0.02.
[0191] Test Case
[0192] The performance tests were performed on the cellulose polymers P1-P8, D1-D3 prepared in Examples 1-8 and Comparative Examples 1-3, and conventional commercially available polyanionic cellulose (LV-PAC, purchased from Shandong Baifeng New Materials Technology Co., Ltd.).
[0193] 1. Evaluation of anti-metal ion (anti-gel) performance
[0194] (1) Take 10 mL of deionized water respectively, and slowly add 0.5 g of P1-P8, D1-D3 and LV-PAC respectively under stirring to completely dissolve them to form a viscous solution;
[0195] (2) Add 5 drops of FeCl 3 Aqueous solution (FeCl 3 The concentration of the aqueous solution is 0.5 mol / L), stirred evenly and allowed to stand for 1 hour;
[0196] (3) Observe the gelation of the sample. The results are shown in Table 1.
[0197] Table 1
[0198] Test samples Whether gel is formed <![CDATA[0.5g P1 + 10mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5 g P2 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5 g P3 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5 g P4 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5g P5 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5g P6 + 10mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5g P7 + 10mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5 g P8 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> no <![CDATA[0.5 g D1 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> yes <![CDATA[0.5 g D2 + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> yes <![CDATA[0.5g D3 + 10mL deionized water + 5 drops of FeCl 3 aqueous solution]]> yes <![CDATA[0.5g LV-PAC + 10 mL deionized water + 5 drops of FeCl 3 aqueous solution]]> yes
[0199] As shown in Table 1, the cellulose polymer containing specific anions and cations provided by the present invention has excellent anti-metal ion ability and is difficult to react with multivalent metal ions such as iron ions to form gel in a water-based environment. In comparison, the anti-gel performance of D1-D3 and LV-PAC is worse than that of P1-P8.
[0200] 2. Evaluation of filtration loss reduction performance
[0201] (1) adding 42 g of sea salt (the composition of sea salt meets GB / T 5005-2010) to 1 L of deionized water to prepare a sea salt solution;
[0202] (2) Take 358 g of the above sea salt solution, add 35 g KCl, 1 g NaHCO 3 After stirring and dissolving fully, add 28g of API standard evaluation soil (purchased from Beijing Mining Exploration Engineering Research Institute) and stir thoroughly;
[0203] (3) 2 g of P1-P8, D1-D3 and LV-PAC as fluid loss reducers were added to the prepared slurry and stirred until completely dissolved;
[0204] (4) Add 3.5 g FeCl to the slurry obtained in step (3) 3 6H 2 O, 2.0 g CuCl 2 ·2H 2 O and 1g anhydrous AlCl 3 , after stirring until completely dissolved, the obtained slurry (respectively recorded as F1-F8, DF1-DF4, where the fluid loss reducer added to DF4 is LV-PAC) was cured in a closed container at 25±1℃ for 16h;
[0205] (5) After the curing, refer to GB / T 5005-2010 to test the API filtration loss of the slurry at 690±35kPa (Note: The filtration loss of the slurry within 7.5-30min is recorded as V 1 The final API loss is twice the V 1 ). The results are shown in Table 2.
[0206] Table 2
[0207]
[0208]
[0209] As can be seen from Table 2, the cellulose polymer containing specific anions and cations provided by the present invention is used as a fluid loss reducer in a water-based drilling fluid system containing multivalent metal ions such as iron ions and copper ions. The fluid loss reduction performance is less affected by high concentrations of metal ions, and the API fluid loss of the drilling fluid can be reduced to less than 16 mL, meeting the fluid loss reduction performance requirements of GB / T 5005-2010 for cellulose fluid loss reducers. However, the fluid loss reducers used in DF1-DF4 are easily complexed with multivalent metal ions in water and then become ineffective, resulting in a large fluid loss in the system.
[0210] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cellulose polymer, characterized in that The polymer comprises: an a-cellulose main body and a plurality of substituent groups -R and -CH2COONa, wherein the substituent groups are connected to part of the hydroxyl oxygen contained in the a-cellulose main body; Wherein, the -R is selected from -C6H 15 ClNO, -C5H 13 ClN and -C6H 15 At least one of ClN; In the polymer, the degree of substitution of -R and -CH2COONa satisfies the following relationship: 0.8≤(DS-CH2COONa+DS -R )≤1.6,DS-CH2COONa / DS -R =1∶(0.05-0.15)。 2. The cellulose-based polymer according to claim 1, wherein -R is selected from -C6H 15 C1NO and / or C6H 15 ClN; Preferably, DS-CH2COONa / DS -R =1∶(0.1-0.15).
3. The cellulose-based polymer according to claim 1 or 2, wherein The degree of polymerization of the cellulose polymer is 70-2600.
4. The cellulose polymer according to any one of claims 1 to 3, wherein The apparent viscosity of the cellulose polymer is 10-2000 mPa·s.
5. A method for preparing a cellulose polymer, characterized in that: include: (1) in the presence of an organic solvent and an alkali solution, subjecting the cellulose raw material to an alkalization treatment to obtain alkalized cellulose; (2) subjecting the alkalized cellulose to a first etherification treatment in the presence of a first etherifying agent to obtain a first product; (3) activating the first etherification product in the presence of an activating agent to obtain a second product; (4) subjecting the second product to a second etherification treatment in the presence of a second etherifying agent to obtain a cellulose polyether polymer.
6. The method according to claim 5, wherein: In step (1), the cellulose raw material is selected from refined cotton or a cellulose extract containing α-cellulose other than refined cotton; Preferably, the degree of polymerization of α-cellulose in the cellulose raw material is 300-2600; Preferably, the alkali solution is an aqueous solution of sodium hydroxide; Preferably, the weight ratio of the organic solvent: the solute alkali in the alkali solution: the cellulose raw material is (8-30): (0.6-1.6): 1; Preferably, the conditions of the alkalization treatment include: temperature of 10-30°C and time of 1-2h.
7. The method according to claim 5 or 6, wherein: In step (2), the first etherifying agent is selected from at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride and 2-chloroethyltrimethylammonium chloride; Preferably, the weight ratio of the first etherifying agent to the cellulose raw material is (0.1-0.25):1; Preferably, the conditions of the first etherification treatment include: temperature of 40-80°C and time of 0.5-3h.
8. The method according to any one of claims 5 to 7, wherein: In step (3), the activator is selected from at least one of triethylammonium chloride, tetraethylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium bromide, benzyltrimethylammonium chloride and benzyltriethylammonium chloride; Preferably, the weight ratio of the activating agent to the cellulose raw material is (0.02-0.1):1; Preferably, the activation treatment conditions include: temperature of 30-50° C. and time of 0.5-1 h.
9. The method according to any one of claims 5 to 8, wherein: In step (4), the second etherifying agent is selected from chloroacetic acid and / or sodium chloroacetate; Preferably, the weight ratio of the second etherifying agent to the cellulose raw material is (0.5-1.8):1; Preferably, the conditions of the second etherification treatment include: temperature of 50-80°C and time of 1-3h.
10. A cellulose-based polymer obtained by the method according to any one of claims 5 to 9.
11. A water-based drilling fluid comprising the cellulose polymer according to any one of claims 1 to 4 and claim 10.
12. Use of the cellulose polymer according to any one of claims 1 to 4 and claim 10 as a fluid loss reducer in drilling fluid.
Citation Information
Patent Citations
Blocky hydroxyethylcellulose, derivatives thereof, process of making, and uses thereof
CN101160350A
Water-soluble, low substitution hydroxyethylcellulose, derivatives thereof, process of making, and uses thereof
CN101171264A
Cellulose-based drilling fluid filtrate reducer and preparation method
CN101602938A
Preparation method of polyanionic cellulose with ultrahigh viscosity for water-based drilling fluid
CN103087202A
Preparation method of polyanionic cellulose
CN104119454A